Synthesis of Antimicrobial Silver Nanoparticle Varnish using Moringa Leaf Bioreductor (Moringa Olifiera): Sintesis Pernis Nanopartikel Perak Anti Mikroba dengan Bioreduktor Daun Kelor (Moringa Olifiera) - Hamid Abdillah; Muhammad Baharits; Rijal Abidin; Firdaus Rizki Biantoro (Jurnal Kimia dan Rekayasa, 2022)
Silver nanoparticles have stable properties and potential applications especially as anti-microbial agents. The growth of fungi and bacteria on the wood surface can be inhibited by varnishing with silver nanoparticles. The nano-silver particles were prepared by synthesizing silver nitrate at concentration of 1, 3, and 5 mM with Moringa oleifera as a bioreductant. PVA (Polyvinyl Alcohol) as a stabilizer was varied at the levels of 0.5%, 1%, and 2%. In the UV-Vis test, the wave peaks are in the range 395-515 nm, this is in accordance with the characteristics of silver nanoparticles. The addition of 1% PVA to silver nanoparticles provided the best stability among the four concentrations provided by evidence of low maximum wavelength shift after storing. Particle size examination using the Particle Size Analyzer (PSA) showed silver nanoparticles had a size of 75.6 nm. Then the silver nanoparticle solution was applied to the resin varnish. The solution of silver nanoparticles has an effect on the antimicrobial properties of resin varnish, as evidenced by the absence of mold growth in the media with silver nanoparticles added. Abstrak Nanopartikel perak memiliki sifat yang stabil dan aplikasi yang potensial khususnya sebagai agen anti-mikroba. Pertumbuhan jamur dan bakteri pada permukaan kayu dapat dihambat dengan pernis yang diberi bahan nanopartikel perak. Partikel nano-perak dibuat melalui sintesis perak nitrat konsentrasi 1, 3, dan 5 mM dengan bioreduktor daun kelor (Moringa oleifera). PVA (Polivinil Alkohol) sebagai stabilsator divariasikan pada kadar 0,5, 1, dan 2%. Pada pengujian UV-Vis, puncak gelombang berada pada rentang 395-515 nm yang sesuai dengan karakteristik nanopartikel perak.  Penambahan PVA 1% pada nanopartikel perak memberikan kestabilan paling baik diantara keempat konsentrasi karena pergeseran panjang gelombang maksimal yang rendah. Pemeriksaan ukuran partikel menggunakan Partikel Size Analyzer ( PSA ) menunjukkan nanopartikel perak memiliki ukuran 75,6 nm. Selanjutnya larutan nanopartikel perak tersebut diaplikasikan pada pernis damar.  Larutan nanopartikel perak berpengaruh terhadap sifat anti mikroba pada pernis damar, dibuktikan dengan tidak tumbuhnya jamur pada media yang ditambahkan nanopartikel perak.